If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6g + -5g + 3g + -3g = 12 Combine like terms: 6g + -5g = 1g 1g + 3g + -3g = 12 Combine like terms: 1g + 3g = 4g 4g + -3g = 12 Combine like terms: 4g + -3g = 1g 1g = 12 Solving 1g = 12 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Divide each side by '1'. g = 12 Simplifying g = 12
| 50-6x=110-46x | | 6-2x=6x-10x/14 | | 3v+2v-3v=12 | | 25(z+750)=-575 | | 11/12-1q/6q-1/3 | | 71-x=85-2x | | 20v-19v=13 | | log(x^2+8)=-2 | | 2ln(2)-ln(1)= | | 3f-2f+f=0 | | 756=21(v+10) | | 10t-t=18 | | 73-2x=83-3x | | 67-x=78-2x | | 7b+23=-47 | | 5y-2[3/2y-5] | | 7c-33=58 | | 3x-3(7x+11)=-153 | | w/8-2=1 | | 66-2x=82-3x | | 9f-(-28)=91 | | 6x+x=2(1+3x)-2(1-x) | | 10g-g=9 | | 8=20-2n | | 4(9+3x)-12=6 | | 4x+1x+4=8x-3x+4 | | X+6+7-5=18+4 | | -14=h+7 | | 5(t-87)=10 | | -5(c-89)=-30 | | 13.7b-3=3.43b | | 74-2x=89-3x |